De segunda pantalla a pantalla principal. `Backup´ el primer programa de televisión creado para Instagram1 - Dra. Dunia ETURA HERNÁNDEZ,Dda. Cristina MARTÍN SÁNCHEZ,Dra. Marta REDONDO GARCÍA (Fonseca, Journal of Communication, 2023)
In recent years, traditional television has been challenged by new media with a predominantly audiovisual character: social networks, VOD platforms, OTT, etc., a competition that affects the mode of consumption and that also influences the approaches, formats and modes of production and dissemination of news contents. In this context, RTVE has been the first Spanish audiovisual group to create an informative series for the Instagram TV social network: BackUp, an investigative program that deals with the most common cybercrimes.